Characterization Of Dicrete Gain Clamped Raman Fiber Amplifier - Ahmad, Asmahanim (2007)

(untitled)
Modern Dense Wavelength Division Multiplexing (DWDM) optical networks consist of add/drop elements to enhance the flexibility of the network. However it introduces transient phenomena which induce Optical signal-to-Noise Ratio (OSNR) degradation and non-linear impairments. Such effect can be alleviated by using Gain-clamped Discrete Raman Fiber Amplifier (GC-DCRFA) which will maintain the gain of the amplifier regardless the input power. The GC-DCRFA in this research work design is realized by utilizing a pair of circulators at the input and output of the amplifier. A portion of counter-propagating amplified spontaneous emission (ASE) is extracted and used to clamp the gain at desired values. The GC-DCRFA is pumped using a pair of 1465 nm Laser Diodes (LD) and input signal wavelength of 1560 nm is used throughout the research work. The GC-DCRFA is also tested using other lasing wavelengths of 1550 nm and 1565 nm. The proposed GC-DCRFA configuration is believed to offer less component losses compared to other amplifier configurations discussed previously. The amplifier characteristics such as the gain and noise figure (NF) are investigated in the research work. The GC-DCRFA is proven to be able to produce a wider dynamic range compared to the conventional DCRFA. For example, at gain of 15 dB, the GC-DCRFA is able to maintain constant gain for input signal, Pin ranges from -25 dBm up to -1.6 dBm with gain variation as of 0.3 dB. On the other hand, the NF is recorded between 5.1 to 6.0 dB. Meanwhile the conventional DCRFA gain starts at 17.8 dB and maintains the gain with the same variation for input signal up to -10 dBm. The effect of adding an Erbium Doped Fiber Amplifier (EDFA) to form a hybrid gain-clamped amplifier configuration is also studied. The hybrid gain-clamped DCRFA/EDFA has wider dynamic range and the availability of maintaining small gain variation. At gain of 15.5 dB, the hybrid gain-clamped DCRFA/EDFA has a dynamic range of between -25 dBm to -1.61 dBm and gain variation of 1.2 dB. Meanwhile for the same dynamic range, the hybrid gain-clamped EDFA/DCRFA generates bigger gain variation of 3.5 dB. However the Noise Figure (NF) seems to be smaller in the hybrid gain-clamped EDFA/DCRFA compared to the other hybrd configuration. The existence of the EDFA seems to influence the dynamic range as it is operating in low pumping regime which causes weak population inversion.